Silicon-containing polymer and bottom anti-reflective coating composition and preparation method thereof
By using a specific structure of silicon polymer and the bottom anti -reflex coating composition, the problem of large changes in anti -reflection coating membrane in the photoresist in the photoresis, and achieved a high etching rate, anti -reflection effect, and membrane thickness stability , Ensure the accuracy of the shape and size of the pattern.
Patent Information
- Application Number
- CN202310427438.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-04-20
AI Technical Summary
The existing silicon-containing photoresist bottom anti-reflective coating has a problem of large film thickness changes during use, resulting in unstable reflectivity and affecting the accuracy of pattern shape and size.
A silicon -containing polymer is composed of a silicon -containing group, cross -linking group, light -absorbing group, and adjustable group group of specific Murbis, and is prepared by free radical polymer reaction. The acidic and solvents form the bottom anti -reflex coating composition.
It achieves high etching rate and anti-reflection effect, while the film thickness changes little, does not dissolve with the photoresist, can effectively eliminate the standing wave phenomenon, and ensures the verticality of the pattern shape and the accuracy of the size.
Smart Images

Figure CN116478328B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoresists, and in particular relates to a silicon-containing polymer and bottom anti-reflective coating composition and a preparation method thereof. Background Art
[0002] In the field of microelectronics, people hope to increase the circuit by reducing the feature size of the structure, which requires lithography manufacturers to provide high-performance lithography technology and high-performance lithography materials. In the currently used light exposure technology, the resolution of the light source wavelength has reached its limit. Previously, mercury lamps were widely used as the light source for photolithography technology, in which g-line (436nm) or i-line (365nm) was used to form the photoresist pattern. In order to obtain finer patterns and shorten the exposure wavelength, short-wavelength KrF excimer laser light (248nm) is used instead of i-line (365nm) as the exposure light source. In the mass production method of 64Mbit DRAM processing, the use of ArF excimer laser (193nm) can provide processing dimensions of 0.13μm or lower.
[0003] In the early days of using KrF excimer laser exposure technology, exposure devices such as achromatic lenses and reflective optical systems have been developed, but the precision of aspherical reflective optical systems is insufficient. Generally, in single-wavelength exposure, the incident light and the reflected light of the substrate interfere to produce standing waves, and the unevenness of the substrate causes light aggregation and light scattering, resulting in halo phenomenon in the pattern. Standing wave phenomenon and halo phenomenon will cause changes in pattern size, line width, etc., and the shape of the pattern will change. Adding light absorbers to the photoresist material can alleviate the standing wave and halo phenomenon to a certain extent, but the addition of light absorbers will change the shape of the pattern (become a cone), and cannot effectively solve the standing wave and halo phenomenon.
[0004] Using an anti-reflection film at the bottom of the photoresist is an effective way to solve standing waves and haloing. Anti-reflection film materials can be divided into inorganic anti-reflection film materials or organic anti-reflection film materials. Among them, inorganic anti-reflection film materials are generally SiON, which is formed into a film by CVD technology, such as using a gas mixture of silane and ammonia water, which has a large etching selectivity relative to the photoresist, but the film formed by this method is not easy to remove and difficult to peel off. Organic anti-reflection film materials can be used by spin coating, eliminating processes such as CVD, can be removed simultaneously with the photoresist, and a relatively straight shape can be obtained. The types of resins in the organic anti-reflection film materials can be phenolic varnish resins, polyhydroxystyrene, polyaliphatic polycyclic skeleton resins, etc., and organic anti-reflection film materials corresponding to different resins have different etching rates. Among them, using silicon-containing polymers as anti-reflection coatings at the bottom of photoresists can provide faster etching rates, have a large etching selectivity relative to photoresists, can eliminate standing wave haloing phenomena, and have vertical pattern shapes. However, silicon-containing polymers all have certain storage stability, and there will be certain changes in film thickness in actual use. For anti-reflective coatings, the anti-reflection effect will change greatly with the change of film thickness. Increasing the molecular weight of the polymer can generally increase the film thickness, but too high a molecular weight will cause pinholes in the pattern and high viscosity will cause problems such as difficulty in filtering. Summary of the invention
[0005] The purpose of the present invention is to overcome the defect of the existing silicon-containing photoresist bottom anti-reflective coating having a large film thickness change during use, and to provide a silicon-containing polymer and bottom anti-reflective coating composition with high etching rate and anti-reflective effect and small film thickness change and a preparation method thereof.
[0006] Specifically, the present invention provides a silicon-containing polymer, wherein the silicon-containing polymer has a structure shown in formula (1):
[0007]
[0008] R1, R3, R5 and R7 are each independently H, optionally substituted C1-C 30 Alkyl or optionally substituted C3-C 20 R2 is a silicon-containing group; R4 is a crosslinkable group; R6 is a light-absorbing group; R8 is H, an optionally substituted C1-C 30 Alkyl, optionally substituted C3-C 20 cycloalkyl or halogen atom; a:b:c:d = (5% to 50%): (10% to 80%): (5% to 80%): (0 to 80%).
[0009] The present invention also provides a method for preparing a silicon-containing polymer, wherein the method comprises subjecting a silicon-containing acrylate monomer represented by formula (3), a first acrylic monomer represented by formula (4), a second acrylic monomer represented by formula (5) and a third acrylic monomer represented by formula (6) in a molar ratio of (5% to 50%): (10% to 80%): (5% to 80%): (0 to 80%) to a free radical polymerization reaction in the presence of an initiator;
[0010]
[0011] R1', R3', R5' and R7' are each independently H, an optionally substituted C1-C 30 Alkyl or optionally substituted C3-C 20 R2' is a silicon-containing group; R4' is a crosslinkable group; R6' is a light-absorbing group; R8' is H, an optionally substituted C1-C 30 Alkyl, optionally substituted C3-C 20 a cycloalkyl group or a halogen atom.
[0012] The present invention also provides a silicon-containing polymer prepared by the above method.
[0013] The present invention also provides a bottom anti-reflective coating composition, wherein the bottom anti-reflective coating composition comprises the above silicon-containing polymer, a cross-linking agent, an acid generator and a solvent.
[0014] The bottom anti-reflection coating composition provided by the invention has a fast etching rate, a small change in film thickness, is not miscible with photoresist, and has the effect of anti-reflection and eliminating standing waves. DETAILED DESCRIPTION
[0015] The silicon-containing polymer provided by the present invention has a structure shown in formula (1):
[0016]
[0017] In formula (1), the molar content of the structural unit derived from the silicon-containing group is represented by a, the molar content of the structural unit derived from the crosslinkable group is represented by b, the molar content of the structural unit derived from the light-absorbing group is represented by c, and the molar content of the structural unit derived from the adjustable group (R8) is represented by d. Based on the total content of a, b, c and d, a is 5% to 50%, such as 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50% or any value therebetween; b is 10% to 80%, such as 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, 101%, 102%, 103%, 104%, 105%, 106%, 107%, 108%, 109%, 110%, 111%, 112%, 113%, 114%, 115%, 116%, 117%, 118%, 119%, 120%, 121%, 122%, 123%, 124%, 125%, 126%, 127%, 128%, 129%, 130%, 131%, 132%, 133%, 134%, 135%, 136 0% or any value therebetween; c is 5% to 80%, such as 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value therebetween; d is 0 to 80%, such as 0, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value therebetween. In addition, formula (1) is only used to represent the type and proportion of each structural unit, and cannot reflect the type of copolymerization reaction and the connection relationship between each structural unit. The silicon-containing polymer can be a random copolymer or a block copolymer.
[0018] In formula (1), R1, R3, R5 and R7 are each independently H, an optionally substituted C1-C 30 Alkyl or optionally substituted C3-C 20 cycloalkyl, preferably each independently H or optionally substituted C1-C5 alkyl. Specific examples of C1-C5 alkyl include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl or neopentyl.
[0019] In formula (1), R2 is a silicon-containing group, preferably having a structure shown in formula (2). 21 , R 22 and R 23 Each is independently H or C1-C5 alkyl. Specific examples of C1-C5 alkyl include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl or neopentyl.
[0020]
[0021] In formula (1), R4 is a crosslinkable group, preferably a hydroxyl group, a carboxyl group, a hydroxyl group substituted by an alkyl group, a carboxyl group substituted by an alkyl group, a hydroxyl precursor, a carboxyl precursor, a hydroxyl precursor substituted by an alkyl group, or a carboxyl precursor substituted by an alkyl group. Among them, the hydroxyl group substituted by an alkyl group is preferably a hydroxyl group substituted by a C1-C5 alkyl group, and examples thereof include a hydroxymethyl group, a hydroxyethyl group, a hydroxyl-n-propyl group, a hydroxyl-isopropyl group, a hydroxyl-n-butyl group, a hydroxyl-isobutyl group, a hydroxyl-tert-butyl group, a hydroxyl-n-pentyl group, a hydroxyl-isopentyl group, a hydroxyl-tert-pentyl group, or a hydroxyl-neopentyl group. Examples of hydroxyl precursors include an epoxy group, an alkoxy group, an acetal group, an acetoxy group, a tert-butoxy group, or a tert-pentyloxy group. The carboxyl group substituted by an alkyl group is preferably a carboxyl group substituted by a C1-C5 alkyl group, and may be -(CH2) n -COOH, wherein n is 1 to 5. Examples of the carboxyl precursor include acid halides, acid anhydrides, esters, and amides, and these carboxyl precursors can be converted into carboxyl groups after hydrolysis.
[0022] In formula (1), R6 is a light-absorbing group, preferably a cyano group, an aniline group, an azo group, an azido group, a sulfone group, a mercapto group, a thioether group, a thioketone group, a nitro group, a nitroso group, an oxime group, a carboxyl group, an ester group, a C6-C 20 Aryl or C6-C 20 Heterocyclic aromatic groups. 20 Specific examples of the aryl group include, but are not limited to, phenyl, phenethyl, ethylphenyl, tolyl, benzyl, xylyl, triphenyl, naphthyl, anthracenyl, alkyl-substituted phenyl, or alkoxy-substituted phenyl. 20 Specific examples of heterocyclic aromatic groups include, but are not limited to, benzofuranyl, benzothiophenyl, quinolyl, isoquinolyl, benzo(1,4)diphenyl Indole or 2,3-dihydrobenzo(1,4)dihydrobenzo English Foundation.
[0023] In formula (1), R8 is H, optionally substituted C1-C 30 Alkyl, optionally substituted C3-C 20 cycloalkyl or halogen atom, preferably H, optionally substituted C1-C5 alkyl, optionally substituted C3-C 10 Specific examples of C1-C5 alkyl include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl or neopentyl. 10 Specific examples of the cycloalkyl group include, but are not limited to, cyclopropyl, cyclohexyl, cyclopentyl, cyclobutyl, cycloheptyl or cyclooctyl. The halogen atom may be F, Cl, Br or I.
[0024] In the present invention, the weight average molecular weight of the silicon-containing polymer is preferably 3000-50000 Daltons, such as 3000, 5000, 8000, 10000, 15000, 20000, 25000, 30000, 35000, 40000, 45000, 50000 or any value therebetween; the molecular weight distribution is preferably 1.6-5, such as 1.6, 2, 2.5, 3, 3.5, 4, 4.5, 5 or any value therebetween.
[0025] The preparation method of the silicon-containing polymer provided by the present invention comprises subjecting a silicon-containing acrylate monomer represented by formula (3), a first acrylic monomer represented by formula (4), a second acrylic monomer represented by formula (5) and a third acrylic monomer represented by formula (6) to free radical polymerization in the presence of an initiator;
[0026]
[0027] R1', R2', R3', R4', R5', R6', R7' and R8' in formula (3) to (6) correspond to R1, R2, R3, R4, R5, R6, R7 and R8 in formula (1), respectively, and the specific selection is not repeated here. R2' preferably has the structure shown in formula (7), wherein R 21 `、R 22 ` and R 23 ` respectively correspond to R in formula (2) 21 , R 22 and R 23 The specific selection will not be described here.
[0028]
[0029] In addition, R4' in the first acrylic monomer provides a reaction site for the polymer, which can undergo a crosslinking reaction with a crosslinking agent. In the present invention, "first", "second" and "third" are only used to distinguish and describe different acrylic monomers and have no other special meanings.
[0030] In the present invention, the molar ratio of the silicon-containing acrylate monomer, the first acrylic monomer, the second acrylic monomer and the third acrylic monomer is (5% to 50%): (10% to 80%): (5% to 80%): (0 to 80%). Based on the total molar content of the silicon-containing acrylate monomer, the first acrylic monomer, the second acrylic monomer and the third acrylic monomer, the molar amount of the silicon-containing acrylate monomer is 5% to 50%, such as 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50% or any value therebetween; the molar amount of the first acrylic monomer is 10% to 80%, such as 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, 101%, 102%, 103%, 104%, 105%, 106%, 107%, 108%, 109%, 110%, 111%, 112%, 113%, 114%, 115%, 116%, 117%, 118%, 119%, 120%, 121%, 122%, 123%, 124%, 125%, 12 %, 65%, 70%, 75%, 80% or any value therebetween; the molar amount of the second acrylic monomer is 5% to 80%, such as 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value therebetween; the molar amount of the third acrylic monomer is 0-80%, such as 0, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value therebetween.
[0031] In the present invention, the conditions of the free radical polymerization reaction include a temperature of preferably 30 to 90° C., such as 30° C., 35° C., 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C. or any value therebetween; and a time of preferably 1 to 10 h, such as 1 h, 3 h, 5 h, 8 h, 10 h or any value therebetween. In addition, the free radical polymerization reaction is generally carried out under the protection of an inert gas.
[0032] In the present invention, the initiator can be selected from at least one of peroxide initiators, azo initiators and redox initiators. Specific examples of the peroxide initiator include, but are not limited to, one or more of hydrogen peroxide, ammonium persulfate, sodium persulfate, potassium persulfate, benzoyl peroxide and tert-butyl benzoyl peroxide. Specific examples of the azo initiator include, but are not limited to, one or more of dimethyl azobisisobutyrate, azobisisobutyramidine hydrochloride, azodicarbonamide, azobisisopropylimidazoline hydrochloride, azoisobutylcyanoformamide, azobiscyclohexylcarbonitrile, azobiscyanovaleric acid, azobisisopropylimidazoline, azobisisobutyronitrile, azobisisovaleronitrile and azobisisoheptylonitrile. Specific examples of the redox initiator include, but are not limited to, one or more of sulfate-sulfite, persulfate-thiourea, persulfate-organic salt and ammonium persulfate-fatty amine. Among them, the sulfate-sulfite can be selected from one or more of sodium sulfate-sodium sulfite, potassium sulfate-potassium sulfite, and ammonium sulfate-ammonium sulfite; the persulfate-thiourea can be selected from one or more of sodium persulfate-thiourea, potassium persulfate-thiourea, and ammonium persulfate-thiourea; the persulfate-organic salt can be selected from one or more of sodium persulfate-potassium acetate, potassium persulfate-potassium acetate, and ammonium persulfate-ammonium acetate; the ammonium persulfate-fatty amine can be selected from one or more of ammonium persulfate-N,N-tetramethylethylenediamine and ammonium persulfate-diethylamine.
[0033] The present invention also provides a silicon-containing polymer prepared by the above method.
[0034] In addition, the present invention also provides a bottom anti-reflective coating composition, which comprises the above-mentioned silicon-containing polymer, a cross-linking agent, an acid generator and a solvent. The content of the silicon-containing polymer is preferably 1 to 20 wt%, the content of the cross-linking agent and the acid generator is preferably 0.1 to 10 wt% each independently, the content of the solvent is preferably 70 to 90 wt%, and the content of the surfactant is preferably 0.01 to 5 wt%.
[0035] In the present invention, the crosslinking agent can be selected from at least one of urea, glycoluril, polymerized glycoluril, melamine, benzocyanuramine, hydroxyalkylamide, epoxy resin, isocyanate, and vinyl ether compounds, preferably glycoluril compounds.
[0036] In the present invention, the acid generator mainly plays the role of promoting the cross-linking reaction of the silicon-containing polymer. The acid generator can be a thermal acid generator (TAG) and / or a photoacid generator (PAG), and can be specifically selected from at least one of a sulfonium salt-based compound, an iodine salt-based compound, a salt-based compound, an organic sulfonic acid, etc. Specific examples of the acid generator include, but are not limited to, dodecylbenzenesulfonic acid, p-toluenesulfonic acid, phthalimido trifluoromethanesulfonate, phthalimido trifluoromethanesulfonate, dinitrobenzyl toluenesulfonate, dinitrobenzyl toluenesulfonate, n-decyl disulfone, naphthyl imino trifluoromethanesulfonate, naphthyl imino trifluoromethanesulfonate, diphenyl iodine trifluoromethanesulfonate, diphenyl iodine perfluorobutyl sulfonate, diphenyl iodine hexafluorophosphate, diphenyl iodine hexafluoroarsenate, diphenyl iodine hexafluoroantimonate, diphenyl p-methoxyphenyl sulfonium trifluoromethanesulfonate, diphenyl p-toluenesulfonium trifluoromethanesulfonate, diphenyl At least one of p-tert-butylphenylsulfonium trifluoromethanesulfonate, diphenylp-isobutylphenylsulfonium trifluoromethanesulfonate, triphenylsulfonium trifluoromethanesulfonate, tri(p-tert-butylphenyl)sulfonium trifluoromethanesulfonate, diphenylp-methoxyphenylsulfonium perfluorobutylsulfonate, diphenylp-tolylsulfonium perfluorobutylsulfonate, diphenylp-tert-butylphenylsulfonium perfluorobutylsulfonate, diphenylp-isobutylphenylsulfonium perfluorobutylsulfonate, triphenylsulfonium perfluorobutylsulfonate, tri-p-tert-butylphenylsulfonium perfluorobutylsulfonate, hexafluoroarsenate, hexafluoroarsenate, triphenylsulfonium hexafluoroantimonate and dibutylnaphthylsulfonium trifluoromethanesulfonate.
[0037] In the present invention, the solvent can be selected from at least one of benzene, toluene, xylene, acetone, methanol, ethanol, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether, ethylene glycol monohexyl ether, diethylene glycol monohexyl ether, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol diacetate, methoxymethyl acetate, ethyl acetate, butyl acetate, ethyl lactate, dibutyl ether, tetrahydrofuran, and gamma-butyrolactone, and is preferably selected from at least one of propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, and ethyl lactate.
[0038] In the present invention, specific examples of the surfactant include, but are not limited to: polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether, and polyoxyethylene oleyl ether; polyoxyethylene alkyl aryl ether surfactants such as polyoxyethylene octylphenol ether and polyoxyethylene nonylphenol ether; sorbitan fatty acid ester surfactants such as sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan monotrioleate, and sorbitan tristearate; and at least one of polyoxyethylene sorbitan fatty acid ester surfactants such as polyoxyethylene-sorbitan monolaurate, polyoxyethylene-sorbitan monopalmitate, polyoxyethylene-sorbitan monostearate, polyoxyethylene-sorbitan monotrioleate, and polyoxyethylene-sorbitan tristearate.
[0039] The bottom anti-reflection coating composition provided by the present invention can be coated on a substrate by, for example, dipping, spin coating or spraying, and baked to solidify it to obtain a bottom anti-reflection coating. Wherein, the substrate can be various substrates known in the art, such as a planar substrate or a substrate with holes. The baking temperature is preferably 100° C. to 250° C., more preferably 100° C. to 180° C. The thickness of the bottom anti-reflection coating is preferably 20nm to 400nm. After the bottom anti-reflection coating is formed, a photoresist composition needs to be coated on the bottom anti-reflection coating and solidified to form a photoresist layer.
[0040] The present invention will be described in detail below through examples.
[0041] Synthesis Example 1 Synthesis of Silicon-Containing Polymer
[0042] 25 g of trimethylsilyl methacrylate, 15 g of methacrylic acid, 5 g of benzyl methacrylate, 5 g of 9-anthracenemethyl methacrylate and 100 g of propylene glycol ethyl ether (PGEE) were placed in a 250 mL three-necked flask equipped with a condenser and a thermometer, and nitrogen was introduced for protection. The mixture was stirred at 30°C for 10 min, and then the temperature was raised to 60°C. 0.15 g of azobisisobutyronitrile was dissolved in 10 mL of propylene glycol ethyl ether and the resulting solution was dropped into the three-necked flask containing the reaction solution within 30 min to react for 3 h. The mixture was then heated to 80°C and kept warm for 3 h. After the reaction was completed, the reaction solution was cooled to room temperature. The resulting transparent viscous liquid was a silicon-containing polymer (denoted as Si@P-1, whose structural formula is shown below), Mw: 12000, PDI: 2.1.
[0043]
[0044] Synthesis Example 2 Synthesis of Silicon-Containing Polymer
[0045] 25 g of trimethylsilyl methacrylate, 10 g of methacrylic acid, 5 g of tert-butyl methacrylate, 5 g of benzyl methacrylate and 100 mL of propylene glycol ether were placed in a three-necked flask equipped with a condenser and a thermometer, and nitrogen was introduced for protection. The mixture was stirred at 30°C for 10 min, and then the temperature was raised to 60°C. 0.15 g of azobisisobutyronitrile was dissolved in 10 mL of propylene glycol ether and the resulting solution was dropped into the three-necked flask containing the reaction solution within 30 min to react for 3 h. The mixture was then heated to 80°C and kept warm for 4 h. After the reaction was completed, the reaction solution was cooled to room temperature. The resulting transparent viscous liquid was a silicon-containing polymer (denoted as Si@P-2, with the structural formula shown below), Mw: 12600, PDI: 2.19.
[0046]
[0047] Synthesis Example 3 Synthesis of Silicon-Containing Polymer
[0048] Dissolve 25g of trimethylsilyl methacrylate, 10g of hydroxypropyl methacrylate, 10g of methacrylic acid, and 5g of benzyl methacrylate in 100mL of propylene glycol ether, pass nitrogen protection, stir at 30°C for 10min, then heat to 60°C for 30min, and dissolve 0.15g of AIBN in PGEE and drop it into the reaction system within 30min, heat for 3h, then heat to 80°C for 4h, and cool to room temperature. The resulting transparent viscous liquid is a silicon-containing polymer (denoted as Si@P-3, whose structural formula is shown below), Mw: 11800, PDI: 2.14.
[0049]
[0050] Synthesis Example 4 Synthesis of Silicon-Containing Polymer
[0051] 10 g of benzyl methacrylate, 5 g of glycidyl methacrylate and 10 g of methacrylic acid were dissolved in 100 mL of propylene glycol ether, nitrogen was introduced, the mixture was stirred at 30 °C and then heated to 60 °C, and the mixture was kept at 60 °C for 30 min. 0.2 g of AIBN was dissolved in propylene glycol ether, and the resulting solution was dropped into the reaction system within 30 min, and the mixture was kept at this temperature for 3 h. Then 10 g of trimethylsilyl methacrylate was added. 0.1 g of AIBN was dissolved in propylene glycol ether and dropped into the reaction system with a constant pressure funnel within 30 min, and the mixture was kept at this temperature for 1 h. The mixture was then heated to 80 °C for 4 h. After the reaction was completed, the mixture was cooled to room temperature. The resulting transparent viscous liquid was a silicon-containing polymer (denoted as Si@P-4, whose structural formula is shown below), Mw: 11600, PDI: 2.12.
[0052]
[0053] Synthesis Example 5 Synthesis of Silicon-Containing Polymer
[0054] 15 g of hydroxypropyl methacrylate, 10 g of tert-butyl methacrylate and 10 g of benzyl methacrylate were dissolved in 100 mL of propylene glycol ether, nitrogen was introduced, the mixture was stirred at 30 °C and then heated to 60 °C, and the mixture was kept at 60 °C for 30 min. 0.2 g of AIBN was dissolved in propylene glycol ether and dripped into the reaction system within 30 min, and the mixture was kept at this temperature for 3 h. Then 10 g of trimethylsilyl methacrylate was added. 0.1 g of AIBN was dissolved in propylene glycol ether and dripped into the reaction system with a constant pressure funnel within 30 min, and the mixture was kept at this temperature for 1 h. The mixture was then heated to 80 °C for 4 h. After the reaction was completed, the mixture was cooled to room temperature. The resulting transparent viscous liquid was a silicon-containing polymer (denoted as Si@P-5, with the structural formula shown below), Mw: 12640, PDI: 2.18.
[0055]
[0056] Comparative Synthesis Example 1 Synthesis of Reference Polymer
[0057] A reference polymer was prepared according to the method of Synthesis Example 5, except that trimethylsilyl methacrylate was not added, and the remaining conditions were the same as those of Synthesis Example 5. The specific steps are as follows:
[0058] 15 g of hydroxypropyl methacrylate, 10 g of tert-butyl methacrylate and 10 g of benzyl methacrylate were dissolved in 100 mL of propylene glycol ether, nitrogen was introduced, and the mixture was stirred at 30 °C and then heated to 60 °C. The mixture was kept at 60 °C for 30 min. 0.2 g of AIBN was dissolved in propylene glycol ether and dripped into the reaction system within 30 min. The mixture was kept at 80 °C for 4 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a transparent viscous liquid, which was the reference polymer (denoted as DSi@P-1, with the structural formula shown below), Mw: 14000, PDI: 2.15.
[0059]
[0060] Comparative Synthesis Example 2 Synthesis of Reference Polymer
[0061] 15 g of hydroxypropyl methacrylate, 10 g of benzyl methacrylate and 5 glycidyl methacrylate were dissolved in 100 mL of propylene glycol ethyl ether, nitrogen was introduced, and the mixture was stirred at 30 °C and then heated to 60 °C. The mixture was kept at 60 °C for 30 min. 0.2 g of AIBN was dissolved in propylene glycol ethyl ether and dropped into the reaction system within 30 min. The mixture was kept at 80 °C for 4 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a transparent viscous liquid (DSi@P-2, with the structural formula shown below) with Mw: 13630 and PDI: 2.1.
[0062]
[0063] Comparative Synthesis Example 3 Synthesis of Reference Polymer
[0064] A reference polymer was prepared according to the method of Synthesis Example 5, except that hydroxypropyl methacrylate and tert-butyl methacrylate were replaced by benzyl methacrylate in equal parts by weight, and the remaining conditions were the same as those of Synthesis Example 5. The specific steps are as follows:
[0065] 45 g of benzyl methacrylate was dissolved in 100 mL of propylene glycol ether, nitrogen was introduced, and the mixture was stirred at 30 °C and then heated to 60 °C. The mixture was kept at 60 °C for 30 min. 0.2 g of AIBN was dissolved in propylene glycol ether and dripped into the reaction system within 30 min. The mixture was kept at this temperature for 3 h. Then 10 g of trimethylsilyl methacrylate was added. 0.1 g of AIBN was dissolved in propylene glycol ether and dripped into the reaction system with a constant pressure funnel within 30 min. The mixture was kept at this temperature for 1 h. The mixture was then heated to 80 °C for 4 h. After the reaction was completed, the mixture was cooled to room temperature. The obtained transparent viscous liquid was the silicon-containing polymer (denoted as DSi@P-3) with Mw: 12061 and PDI: 2.19.
[0066] Examples 1-5 and Comparative Examples 1-3
[0067] The polymers obtained in the above synthesis examples and comparative synthesis examples, the crosslinking agent, the acid generator and the solvent were prepared into a bottom anti-reflective coating composition. The amount of each component is shown in Table 1.
[0068] In Table 1, the types of components are as follows:
[0069] Cross-linking agent: Tetramethoxymethyl glycoluril, the structural formula of which is shown below:
[0070]
[0071] Acid generator: (4-hydroxyphenyl) diphenylsulfonium trifluoromethanesulfonic acid, the structural formula of which is shown below:
[0072]
[0073] Surfactant: purchased from 3M, brand FC430;
[0074] Solvent: Propylene glycol ethyl ether.
[0075] The anti-reflective coating composition was applied onto a silicon wafer and baked at 200° C. for 120 s to obtain a bottom anti-reflective coating film. The refractive index n and extinction coefficient k of the bottom anti-reflective coating film at 193 nm were measured using an ellipsometer (manufacturer: JA Woolam, equipment name: VUV-303).
[0076] Table 1
[0077]
[0078] It can be seen from the data in Table 1 that the bottom anti-reflective coating compositions prepared by Examples 1 to 5 and Comparative Examples 1 to 3 have a refractive index n value between 1.5 and 1.9 at 193 nm and an absorption coefficient k value greater than 0.15, indicating that they have an effective anti-reflective effect. However, the Examples have higher refractive index and absorption coefficient than the Comparative Examples, and the film thickness change after three months is also smaller.
[0079] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A bottom anti-reflective coating composition, characterized in that: The bottom anti-reflective coating composition contains a silicon-containing polymer, a cross-linking agent, an acid generator, a solvent, and an optional surfactant, wherein the silicon-containing polymer has a structure shown in formula (1): Formula (1) R1, R3, R5 and R7 are each independently H, optionally substituted C1-C 30 Alkyl or optionally substituted C3-C 20 R2 is a silicon-containing group; R4 is a crosslinkable group; R6 is a light-absorbing group; R8 is H, an optionally substituted C1-C 30 Alkyl, optionally substituted C3-C 20 cycloalkyl or halogen atom; a:b:c:d=(5%~50%):(10%~80%):(5%~80%):(0~80%).
2. The bottom anti-reflective coating composition according to claim 1, characterized in that R1, R3, R5 and R7 are each independently H or an optionally substituted C1-C5 alkyl group; R2 has the structure shown in formula (2); R4 is a hydroxyl group, a carboxyl group, a hydroxyl group substituted with an alkyl group, a carboxyl group substituted with an alkyl group, a hydroxyl group precursor, a carboxyl group precursor, a hydroxyl group precursor substituted with an alkyl group or a carboxyl group precursor substituted with an alkyl group; R6 is a cyano group, an aniline group, an azo group, an azido group, a sulfone group, a mercapto group, a thioether group, a thioketone group, a nitro group, a nitroso group, an oxime group, a carboxyl group, an ester group, a C6-C 20 R8 is H, optionally substituted C1-C5 alkyl, optionally substituted C3-C 10 a cycloalkyl group or a halogen atom; Formula (2) R 21 , R 22 and R 23 Each is independently H or C1-C5 alkyl.
3. The bottom anti-reflective coating composition according to claim 1, characterized in that The weight average molecular weight of the silicon-containing polymer is 3000-50000 Daltons, and the molecular weight distribution is 1.6-5.
4. The bottom anti-reflective coating composition according to claim 1, characterized in that The silicon-containing polymer is prepared according to the following method: a silicon-containing acrylate monomer represented by formula (3), a first acrylic monomer represented by formula (4), a second acrylic monomer represented by formula (5) and a third acrylic monomer represented by formula (6) are subjected to a free radical polymerization reaction in the presence of an initiator in a molar ratio of (5% to 50%): (10% to 80%): (5% to 80%): (0 to 80%); Formula (3), Formula (4), Formula (5), Formula (6), R1', R3', R5' and R7' are each independently H, optionally substituted C1-C 30 Alkyl or optionally substituted C3-C 20 R2' is a silicon-containing group; R4' is a crosslinkable group; R6' is a light-absorbing group; R8' is H, an optionally substituted C1-C 30 Alkyl, optionally substituted C3-C 20 a cycloalkyl group or a halogen atom.
5. The bottom anti-reflective coating composition according to claim 4, characterized in that R1', R3', R5' and R7' are each independently H or an optionally substituted C1-C5 alkyl group; R2' has the structure shown in formula (7); R4' is a hydroxyl group, a carboxyl group, a hydroxyl group substituted with an alkyl group, a carboxyl group substituted with an alkyl group, a hydroxyl group precursor, a carboxyl group precursor, a hydroxyl group precursor substituted with an alkyl group or a carboxyl group precursor substituted with an alkyl group; R6' is a cyano group, an aniline group, an azo group, an azido group, a sulfone group, a mercapto group, a thioether group, a thioketone group, a nitro group, a nitroso group, an oxime group, a carboxyl group, an ester group, a C6-C 20 Aryl or C6-C 20 R8' is H, optionally substituted C1-C5 alkyl, optionally substituted C3-C 10 a cycloalkyl group or a halogen atom; Formula (7) R 21 `、R 22 ` and R 23 `Each independently is H or C1-C5 alkyl.
6. The bottom anti-reflective coating composition according to claim 4, characterized in that The conditions of the free radical polymerization reaction include a temperature of 30-90° C. and a time of 1-10 h.
7. The bottom anti-reflective coating composition according to claim 4, characterized in that The initiator is selected from at least one of a peroxide initiator, an azo initiator and a redox initiator.
8. The bottom anti-reflective coating composition according to claim 1, characterized in that The cross-linking agent is a glycoluril compound; the acid generator is a thermal acid generator and / or a photoacid generator; the solvent is selected from at least one of propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether and ethyl lactate; the surfactant is selected from at least one of polyoxyethylene alkyl aryl ether surfactants, sorbitan fatty acid ester surfactants and polyoxyethylene sorbitan fatty acid ester surfactants.
Citation Information
Patent Citations
Aqueous ink, ink cartridge, and inkjet recording method
JP2018150413A
Inkjet recording method and inkjet recording apparatus
JP2019014238A